2016
DOI: 10.1200/jgo.2016.003749
|View full text |Cite
|
Sign up to set email alerts
|

HPV Testing of Self-Collected Vaginal Swabs for Cervical Cancer Prevention in South Africa

Abstract: 33 Background: Cervical cancer screening programs in Low and Middle Income Countries (LMIC) need to be strengthened. One of the challenges is insufficient health care personnel to achieve optimal coverage. We evaluated the potential of human papillomavirus (HPV) testing using self-collected vaginal swabs to improve screening. Methods: As part of a larger NCI-supported study in Cape Town, South Africa, we recruited 261 HIV-uninfected and 237 HIV-infected women aged 30-60 years, at one primary health care site. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…We demonstrated that restricting to specific HPV types and tolerating less stringent cut-offs for detecting HPV can lead to substantial improvements in specificity while maintaining adequate sensitivity. 20 These improvements in specificity could even be attained in HIV-positive women – a group known to have very high prevalences of HPV infection. 20 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that restricting to specific HPV types and tolerating less stringent cut-offs for detecting HPV can lead to substantial improvements in specificity while maintaining adequate sensitivity. 20 These improvements in specificity could even be attained in HIV-positive women – a group known to have very high prevalences of HPV infection. 20 …”
mentioning
confidence: 99%
“…20 These improvements in specificity could even be attained in HIV-positive women – a group known to have very high prevalences of HPV infection. 20 …”
mentioning
confidence: 99%